Effect of dietary microalgae on growth performance and health in meat-type quails - Samar M. Mohamed; Mahmoud Alagawany; Mohamed S. El-Kholy; Mohamed M. El-Mekkawy; Ayman S. Salah; Youssef A. Attia; Rashed A. Alhotan; Alessandro Di Cerbo; Antonia Lestingi (Poultry Science)
The purpose of this work was to ascertain the impact of dietary inclusion of Dunaliella salina (Ds) and Arthrospira platensis (Ap) mixture as growth promoters on growth performance, carcass traits, liver and renal function, lipid profile, immunology and economics in quail chicks. 240 Un -sexed seven-day quail chicks were separated into four treatment groups with six replicates of ten chicks per group. The treatment groups are: control: basal diet; DsAp0.5: basal diet + 0.25 g Ds+ 0.25 g Ap/kg diet; DsAp1: basal diet + 0.50 g Ds+ 0.50 g Ap/kg diet; and DsAp2: basal diet + 1.00 g Ds+ 1.00 g Ap/kg diet. The outcomes of dietary inclusion of Ds plus Ap revealed a significant difference in live body weight at 5 week and body weight gain from (1-5wk) (P=0.049) and the group DsAp1 recorded the best results (191.19g, 5.69g). The mixture of Ds plus Ap did not significantly (P>0.05) change the feed intake during the experiment. The DsAp0.5 group significantly (P=0.019) presented the best feed conversion ratio during (1-5 wk of age) compared to the control and other groups. The finding showed a non-significant difference in carcass traits (P>0.05). Liver and kidney function markers were affected by the supplements, and DsAp2 group recorded the highest levels of total protein and albumin. The DsAp1 group significantly (P=0.003) presented the lowest level of alanine aminotransferase (ALT) and the DsAp2 group significantly (P<0.001) presented the lowest levels of aspartate aminotransferase (AST) and urea. Dietary supplementation of Ds plus Ap affected the lipid profiles of the quail. Dietary supplementation of Ds plus Ap mixture reduced the concentration of total cholesterol (TC), low-density lipoprotein (LDL), triglyceride (TG) and high-density lipoprotein (HDL) when compared to control (P<0.001). Furthermore, the immune parameters, complement 3 (C3) and lysozyme showed a non-significant variation with Ds plus Ap supplementation. The net revenue and economic efficiency of treated quails was significantly increased during the experiment (1-5 wks of age); the best values were observed in DsAp0.5 group. In conclusion, the use of Ds plus Ap mixture as growth promoters in quail diets improves the growth performance, liver functions and lipid profile.